Oxidation regularities of the electroexplosive metal nanopowders during heating in air after microwave irradiation; Journal of Thermal Analysis and Calorimetry; Vol. 150, iss. 4 - Mostovshchikov A. V. Andrey Vladimirovich; Nazarenko O. B. Olga Bronislavovna; Derina K. V. Kseniya Vladimirovna; Zinicovscaia I. Inga (2025, 2025)
Title screen